A Study on Determining Weld Joint Hardening and a Quality Evaluation Algorithm for 9% Nickel Weld Joints Using the Dilution Ratio of the Base Material in Fiber Laser Welding - Minho Park; Jisun Kim; Changmin Pyo; Jaewoong Kim; Kwangsan Chun (Metals, 2021)
The demand for LNG-powered ships and related equipment is rapidly increasing among major domestic and foreign carriers due to the strengthened IMO regulations on the sulfur content of ship fuel oil. LNG operation in a cryogenic environment requires a storage tank and fuel supply system that uses steel with excellent brittleness and fatigue strength. A ship using LNG is very sensitive to explosion and fire. For this reason, 9% Ni is often used, because ships require high quality products with special materials and structural technologies that ensure operability at cryogenic temperatures. However, research to derive uniform welding quality is urgent because the deterioration of weld quality in the 9% Ni steel welding process is caused by high process difficulty and differences in welding quality depending on a welder’s skill set. This study proposes a method to guarantee a uniform quality of 9% Ni steel in a fiber laser welding process by categorizing weld joint hardness according to the dilution ratio of a base material and establishing a standard for quantitative evaluation.